Manajemen Pelayanan Komputer Job Access with Speech (JAWS) bagi Mahasiswa Tuna Netra di Pusat Layanan Difabel (PLD) UIN Sunan Kalijaga Yogyakarta - Kuzaemah Kuzaemah; Edy Yusuf Nur SS (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2017)
This research is one of the efforts to meganalisis computer services management how JAWS for tuna netra students at PLD UIN Sunan KalijagaYogyakarta. This research is a research field that uses a qualitative approach. Data collection is done by holding observation, interviews, and documentation. Data analysis was done by giving meaning to the data that was successfully collected and of the meaning that's drawn the conclusion. The results of this study showed that computer Services Management JAWS in PLD UIN Sunan Kalijaga Yogyakarta include some of the functions of management, planning, i.e. the first Chairman of the PLD menentukian schedule of activities. Second, i.e. organizing Chairman of the PLD task from the masingmasing position. Third, the implementation of PLD members who have been given the task by doing their job. Fourth, i.e. surveillance of all activities in the PLD are always monitored and held a meeting of rutinan in order to know the problems encountered so that it can be solved together. The benefits of computer services i.e. JAWS add technological knowledge for students to make tuna and tuna netra student self-reliance in doing tasks lectures relating to penegtikan as well as the task of term papers, thesis etc. As for the supporting factors of the implementation pellayanan JAWS computer namely tuna netra student zeal and the help of the volunteers PLD. To factor penghambatnya i.e. the number of computers the JAWS are very limited so they must alternately in using it.